2007
DOI: 10.1080/14789940701491370
|View full text |Cite
|
Sign up to set email alerts
|

Homicide-suicide in the Netherlands: A study of newspaper reports, 1992 – 2005

Abstract: Background: Homicides followed by the suicide of the perpetrator are a rare yet very serious form of interpersonal violence which occurs mainly in partnerships and families. It typically leads to widespread public interest and unease. No systematic research on homicide suicide has ever been conducted in the Netherlands. Aim: The aim of this study is to describe the nature and incidence of homicide suicide in the Netherlands in the period 1992 2005, using cases reported in both national and regional newspapers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 20 publications
4
39
0
9
Order By: Relevance
“…In England and Wales it is estimated that homicide-suicide accounts for 1% of all homicides (Barraclough 2002). A Dutch study found that a firearm was the most frequently used method for the homicide and the suicide and that 23% of perpetrators failed in their suicide attempt (Liem 2007). Homicide-suicide has been commonly associated with depression and one case series found that 75% of perpetrators were depressed at the time (Rosenbaum 1990).…”
Section: Depression and Homicide-suicidementioning
confidence: 99%
“…In England and Wales it is estimated that homicide-suicide accounts for 1% of all homicides (Barraclough 2002). A Dutch study found that a firearm was the most frequently used method for the homicide and the suicide and that 23% of perpetrators failed in their suicide attempt (Liem 2007). Homicide-suicide has been commonly associated with depression and one case series found that 75% of perpetrators were depressed at the time (Rosenbaum 1990).…”
Section: Depression and Homicide-suicidementioning
confidence: 99%
“…De term filicide behelst het doden van een kind ouder dan één jaar. Filicide wordt tevens vaak gebruikt als een verzamelnaam voor kinderdodingen gepleegd door de vader of moeder (Brants & Koenraadt 1998;Koenraadt & Liem 2007). Bij de bestudering van kinderdoding dient een belangrijk onderscheid te worden gemaakt tussen intra-familiale kinderdodingen, waarbij een kind door een familielid of verzorger wordt gedood, en extra-familiale kinderdodingen, waarbij een kind door een buitenstaander wordt gedood.…”
Section: Inleidingunclassified
“…Bij de bestudering van kinderdoding dient een belangrijk onderscheid te worden gemaakt tussen intra-familiale kinderdodingen, waarbij een kind door een familielid of verzorger wordt gedood, en extra-familiale kinderdodingen, waarbij een kind door een buitenstaander wordt gedood. Waar bij de laatstgenoemde categorie vaak wordt gehandeld vanuit een seksueel motief, is hiervan zelden sprake bij intra-familiale kinderdodingen (Koenraadt 2003;Koenraadt & Liem 2007). Gezien de relatief lage incidentie van extra-familiale kinderdodingen en de grote verschillen tussen beide typen kinderdodingen, richten we ons in dit onderzoek op intra-familiale kinderdodingen.…”
Section: Inleidingunclassified
See 2 more Smart Citations